2014
DOI: 10.1016/j.antiviral.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Yeast-based assays for the high-throughput screening of inhibitors of coronavirus RNA cap guanine-N7-methyltransferase

Abstract: The 5'-cap structure is a distinct feature of eukaryotic mRNAs and is important for RNA stability and protein translation by providing a molecular signature for the distinction of self or non-self mRNA. Eukaryotic viruses generally modify the 5'-end of their RNAs to mimic the cellular mRNA structure, thereby facilitating viral replication in host cells. However, the molecular organization and biochemical mechanisms of the viral capping apparatus typically differ from its cellular counterpart, which makes viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 53 publications
1
56
0
Order By: Relevance
“…This observation is corroborated by former biochemical data showing that the N7-methyl guanosine of cap structures is recognized by the eukaryotic translation initiation factor 4E (eIF4E) and participates in the initiation of viral mRNA translation into proteins (Case et al, 2016;Cougot et al, 2004). Accordingly, inhibitors blocking nsp14 N7-MTase activity have been identified by yeast based screening assay on SARS-CoV, and induced a potent antiviral effect demonstrating that nsp14 MTase activity is an attractive antiviral target (Sun et al, 2014). Whereas N7-MTase mutants are replication defective, 2 0 O-MTase mutants show limited effect on virus replication in cell culture but have an attenuated phenotype in animal models Menachery et al, 2014;Zhang et al, 2014;ZĂŒst et al, 2013).…”
Section: Introductionsupporting
confidence: 62%
“…This observation is corroborated by former biochemical data showing that the N7-methyl guanosine of cap structures is recognized by the eukaryotic translation initiation factor 4E (eIF4E) and participates in the initiation of viral mRNA translation into proteins (Case et al, 2016;Cougot et al, 2004). Accordingly, inhibitors blocking nsp14 N7-MTase activity have been identified by yeast based screening assay on SARS-CoV, and induced a potent antiviral effect demonstrating that nsp14 MTase activity is an attractive antiviral target (Sun et al, 2014). Whereas N7-MTase mutants are replication defective, 2 0 O-MTase mutants show limited effect on virus replication in cell culture but have an attenuated phenotype in animal models Menachery et al, 2014;Zhang et al, 2014;ZĂŒst et al, 2013).…”
Section: Introductionsupporting
confidence: 62%
“…Biochemical assays demonstrated that ATA inhibits both nsp14 N7-MTase and nsp16 2 -O-MTase activities . Recently, Sun et al (2014) developed a yeast-based high-throughput antiviral screening system to find novel anti-coronavirus drugs. This study confirmed that sinefungin significantly suppresses the growth of yeast cells complemented with nsp14 N7-MTase gene.…”
Section: The 2 -O-methyltransferase (2 -O-mtase)mentioning
confidence: 99%
“…This study confirmed that sinefungin significantly suppresses the growth of yeast cells complemented with nsp14 N7-MTase gene. However, sinefungin is not a specific inhibitor as it also inhibits yeast and human MTases (Sun et al, 2014).…”
Section: The 2 -O-methyltransferase (2 -O-mtase)mentioning
confidence: 99%
“…ATA was also shown to limit SARS-CoV replication in infected cells (He et al, 2004). In the yeast-△MTase trans-complementation assay mentioned earlier, micromolar concentrations of sinefungin were reported to effectively suppress the nsp14 N7-MTase activity of SARS-CoV, MHV, transmissible gastroenteritis virus (TGEV), and IBV (Sun et al, 2014). However, other compounds, such as ATA and AdoHcy, did not exert an inhibitory effect in the context of yeast cells.…”
Section: The Nsp14 N7-methyl Transferasementioning
confidence: 95%